Makala-Kalaan Tradisi Tua di Desa Suter Kecamatan Kintamani Kabupaten Bangli - I Wayan Yudhasatya Dharma; Armini, Ni Wayan Yusi (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2024)
Education is an effort to improve the quality of human life which essentially aims to humanize humans, mature them and change behavior for the better. Education does not only take place at school, but the environment also takes part in this. The environment is the unity of space with all objects, forces, conditions and living creatures, including humans and their behavior, which influence the lives and welfare of humans and other living creatures. In this social environment, a child begins to socialize with the wider community and begins to become familiar with social norms. Culture is also a system of knowledge and also as ideas that a society has. In relation to culture which actually contains elements of education, there is a tradition called Makala-kalaan Tua which is part of the social life of the community in Suter Village, Kintamani District, Bangli Regency. Through this research, researchers want to analyze the implementation of the Makala-kalaan Tua tradition in terms of educational philosophy. To explain the problem above, the author uses qualitative research. In this case, the author was directly involved in collecting data by means of observation, documentation and interviews with informants in Suter Village. Apart from that, this research uses types of library data such as books, journals, or previously existing scientific works that have a correlation with the research being carried out. To answer the problem, researchers used Constructivism Theory. From the research conducted, findings were obtained, namely that the implementation of the Makala-kalaan Tua tradition in Suter Village, Kintamani District, Bangli Regency in terms of educational philosophy contains elements of activeness, creativity and innovation. Where these three elements constitute the true essence of education. Because in an educational process, activeness is very important because it influences the results of the education itself. Then creativity and innovation are the goals to be achieved in every educational process.